Atividade física e qualidade de vida em pacientes com doença renal crônica submetidos à hemodiálise - Medina, Luiz Antonio Rodrigues; Vanderlei, Franciele Marques [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Torres, Daniele Braz [UNESP]; Padulla, Susimary Aparecida Trevisan [UNESP]; Freitas, Carlos Eduardo Assumpção; Padovani, Carlos Roberto; Gabriel Filho, Luís Roberto Almeida [UNESP]; Betônico, Gustavo Navarro; Lopes, Francis Da Silva (University Nove de Julho, 2010)
Objective: To analyze and correlate the physical activity level (PAL) and the quality of life (QL) in patients with chronic kidney disease (CKD) undergone hemodialyses and to verify in practitioner of physical activity (PPA) if they follow rules and recommendations on their own practice. Methods: The QL (KDQOL-SFTM questionnaire), PAL (IPAQ questionnaire) and the evaluation of rules and recomendations to practice PA were analyzed in one hundred patients. Results: It was observed commitment on different dimensions of QL, higher values to sexual function and social support (88,6) and lower ones to professional paper (25,2) and physical function (47,7). Most patients shows low values of PAL and most PPA implement the exercises incorrectly. It was observed differences between PAL and some areas of QL. Conclusion: Patients with CKD undergone hemodialysis presented low values to PAL, commitment on QL, and most of the patients that realized PA did not implement rules and recomendations on their own practice.

Objetivos: Analisar e correlacionar o nível de atividade física (NAF) e a qualidade de vida (QV) de pacientes com doença renal crônica (DRC) submetidos à hemodiálise, e verificar, nos praticantes de atividades físicas (AF), se eles seguem normas e recomendações adequadas para sua prática. Método: A QV (questionário KDQOL-SFTM), o NAF (questionário IPAQ) e avaliação de normas e recomendações para prática de AF foram analisados em 101 pacientes. Resultados: Foi observado comprometimento nas diferentes dimensões da QV, com os maioresvalores para função sexual e suporte social (88,6), e os menores, para papel profissional (25,2) e função física (47,7). A maioria dos pacientes apresentou baixos NAF, e a maior parte dos praticantes de AF executa exercícios incorretamente. Diferenças entre NAF e alguns domínios da QV foram observadas. Conclusões: Os pacientes com DRC submetidos à hemodiálise apresentaram baixos NAFs e comprometimento na QV, e a maioria dos que realizavam AF não seguiam normas e recomendações adequadas para sua prática.
Physical activity and quality of life in patients with chronic renal disease undergone hemodialysis
Keywords: Hemodiálise; Atividade física; Qualidade de vida; Insuficiência renal crônica